A Universal Formula For Asymptotic Stabilization With Bounded Controls - Kamarudin, Muhammad Nizam; Husain, Abdul Rashid; Ahmad, Mohamad Noh; Mohamed, Zaharuddin (World Academy of Science , Engineering and Technology, 2015)
-